The Newfound Status of English in 21st-Century Saudi Arabia - Al-Seghayer, Khalid (International Journal of Linguistics, 2023)
To keep pace with Saudi Vision 2030, the status of English in Saudi Arabia has undergone rapid changes over the past few years and will continue to change and grow in the future. This article is intended to portray an accurate picture of the contemporary indomitable prominence of English in present-day Saudi Arabia on a variety of fronts. In particular, it identifies the prevalence of English in the overall landscape of Saudi Arabia in light of Saudi Vision 2030, especially in the Saudi education system, in the public perception, in the Saudi workforce, and in Saudi media outlets, as well as its function as the primary language of communication between Saudi citizens and expatriate residents. To this end, this in-depth discussion contributes to a better and deeper understanding of the central role English plays and its prestigious position in Saudi Arabia’s national setup and highlights Saudi Arabia’s newfound appreciation for English as a vital tool to meet its ambitious advancement plans.